2022
DOI: 10.1108/nfs-10-2021-0296
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient variability of rice landraces (Oryza sativa L.) from Manipur, Northeast India and its nutrients supply potential in rice-based diets

Abstract: Purpose Rice landraces are essential for supplying beneficial traits for developing improved rice varieties with better nutritional quality. Nevertheless, in a yield-driven environment, grain nutritional quality has been ignored especially that of rice landraces. Given this, the purpose of this study is to evaluate the content and nutritional variability of rice landraces from Manipur. Design/methodology/approach Thirty-three most popular rice landraces were collected as dry paddy samples from Manipur and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Pyridoxine (0.141-0.181 mg/100 g) and folate (19.277-23.953 mcg/100 g) levels were high in BRRI 84. Most of the varieties examined in the present study showed vitamin content comparable to earlier findings [21] (Supplementary Table S8). This study also examined the effect of parboiling and polishing on vitamin content.…”
Section: Parboiling and Polishing Effect On The Vitamin Content Of Di...supporting
confidence: 90%
“…Pyridoxine (0.141-0.181 mg/100 g) and folate (19.277-23.953 mcg/100 g) levels were high in BRRI 84. Most of the varieties examined in the present study showed vitamin content comparable to earlier findings [21] (Supplementary Table S8). This study also examined the effect of parboiling and polishing on vitamin content.…”
Section: Parboiling and Polishing Effect On The Vitamin Content Of Di...supporting
confidence: 90%